PENERAPAN MODEL KOOPERATIF TIPE MAKE A MATCH DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA BERBANTUAN MEDIA POP UP BOOK PADA PEMBELAJARAN MATEMATIKA KELAS IV SDN 003/IX SENAUNG - Ayuni Shakila; Eka Sastrawati; Issaura Sherly Pamela (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The research describes implementing the cooperative learning model of make a match type, aided by pop-up book media, to boost fourth-grade students' motivation in elementary school mathematics. Conducted as Classroom Action Research, data collection involved observation, interviews, and documentary studies at SD Negeri 003/IX Senaung. Results showed improvement across cycles: in the first cycle, meeting I, 58.3% was categorized as "low," while meeting II was 61.8% "medium"; in the second cycle, meeting I, it rose to 69.8% "high," and meeting II reached 72.1% "high." The study concludes that implementing the Make A Match model with Pop Up Book media aids in enhancing students' motivation in mathematics, aligning with research outcomes.